The Bolognese Tradition: Ancient Tradition or Modern Myth? - Rob Runacres (Acta Periodica Duellatorum)
This article discusses the modern interpretation that Bologna produced a distinctive regional martial tradition, based on the existence of similar treatises. It examines the assumption that a series of fencing masters formed a distinct lineage and that their martial practices formed a tradition separate to martial forms outside of Bologna. As a case study, it also considers the 'Viridario' of Giovanni Filoteo Achillini, a poem that contains instructions on the use of sword an buckler, written in 1504 and asks why this apparently unknown treatise was not used by its author to promote a Bolognese tradition.